The Estimation of Escape Fraction of 𝛂-particle from a Contaminated Deuterium-Tritium Hot-spot - Seyyed Mohammad Eftekhari; Soheil Khoshbinfar (فیزیک کاربردی ایران)
The energy deposition of alpha particles resulting from nuclear fusion of deuterium-tritium (DT) fuel is one of the important challenges in inertial confinement fusion. The stability of ignition conditions is associated with the achievement of self-ignition in hot- spot plasma. Excessive escape of energy from the hot spot leads to its rapid cooling and quenching. In this research, we will examine the contribution of electronic and ionic plasma components in the calculation of the escape fraction and the stopping of charged particles produced by fusion reactions. First, the contribution of small-angle scattering in alpha particle energy loss based on the Krokhin-Rozanov (KR) model and then using the Li- Petrasso stopping power (LP), the cumulative effect of small and large angle scattering in the energy loss of alpha particles in two cases of pure and ion contaminated DT fuel has been investigated numerically. It is shown that in the pre-compressed fuel of fast ignition, the stopping of the electron component of the plasma is dominant only for the high-energy alpha particle. Nevertheless, at the same time as the alpha particle slows down and heats fuelplasma, the stopping contribution of the ion component of the plasma is strengthened and the range of the alpha particle decreases by up to 50% compared to the pure electron case. This effect is intensified by increasing the fuel density and by injecting impurities into the DT fuel plasma environment.